2016
DOI: 10.1002/1873-3468.12059
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of 6‐phospho‐cyclophellitol as a novel probe of 6‐phospho‐β‐glucosidases

Abstract: Edited by Stuart FergusonCovalent, mechanism-based inhibitors of glycosidases are valuable probe molecules for visualizing enzyme activities in complex systems. We, here, describe the chemoenzymatic synthesis of 6-phospho-cyclophellitol and evaluate its behaviour as a mechanism-based inactivator of the Streptococcus pyogenes 6-phospho-b-glucosidase from CAZy family GH1. We further present the three-dimensional structure of the inactivated enzyme, which reveals the constellation of active site residues responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…To date, ABPs have been reported that enable selective profiling of retaining glycosidases such as β‐glucosidases, α‐glucosidases, α‐galactosidases[29b] and α‐fucosidases, which are designed based on compound 2 bearing N‐substituents featuring a fluorophore or biotin as a reporter entity. Cyclophellitol‐aziridine ( 2 ) has proven to be a superior scaffold compared to 2 (or 5)‐deoxy‐5‐fluoroglycosides for in vitro and in situ ABPP of retaining β‐glucosidase activities and adaptation of the configuration and substitution pattern will likely yield selective ABPs for retaining glycosidase families evolved to recognize and hydrolyze the underlying configurational carbohydrates – next to monosaccharides (exoglycosidases) likely also oligosaccharides (endoglycosidases). To fulfil this promise, though, synthetic methodology needs to be expanded to enable easy access to an array of configurational and functional cyclophellitol/cyclophellitol‐aziridine analogues.…”
Section: Discussionmentioning
confidence: 99%
“…To date, ABPs have been reported that enable selective profiling of retaining glycosidases such as β‐glucosidases, α‐glucosidases, α‐galactosidases[29b] and α‐fucosidases, which are designed based on compound 2 bearing N‐substituents featuring a fluorophore or biotin as a reporter entity. Cyclophellitol‐aziridine ( 2 ) has proven to be a superior scaffold compared to 2 (or 5)‐deoxy‐5‐fluoroglycosides for in vitro and in situ ABPP of retaining β‐glucosidase activities and adaptation of the configuration and substitution pattern will likely yield selective ABPs for retaining glycosidase families evolved to recognize and hydrolyze the underlying configurational carbohydrates – next to monosaccharides (exoglycosidases) likely also oligosaccharides (endoglycosidases). To fulfil this promise, though, synthetic methodology needs to be expanded to enable easy access to an array of configurational and functional cyclophellitol/cyclophellitol‐aziridine analogues.…”
Section: Discussionmentioning
confidence: 99%
“…19 Cyclophellitol-derived ABPs have been used to probe β- and α-glucosidases in tissue samples from Gaucher 20 and Pompe 21 disease patients, respectively. We have also reported the use of cyclophellitol-derived ABPs in the discovery and quantification of α- l -fucosidases, 22 6-phospho-β -d- glucosidases, 23 and β -d- glucuronidases in the context of heparan degradation. 24…”
Section: Introductionmentioning
confidence: 99%
“…25 Analogues 12–15 were examined as substrates of Glk, utilizing conditions described in the literature. 32 Recombinant Glk was found to efficiently convert all four C-1 fluoromethyl-modified G1P analogues ( 12–15 ) to corresponding 7-phosphorylated products. This result demonstrates that Glk tolerates a glucopyranose sugar modified at the anomeric center.…”
Section: Resultsmentioning
confidence: 99%
“…This followed the literature procedure with minor modifications. 32 A final volume of 4 mL (50 mM Tris–HCl, pH 7. 5) comprising 1-deoxy-α- d -glucoheptuloses (50 μM), MgCl 2 (102 mg, 500 μM), ATP (200 mM, 500 μL), and recombinant E. coli Glk (28 mg mL –1 , 110 μL) was incubated at 37 °C overnight.…”
Section: Experimental Sectionmentioning
confidence: 99%